Bending energy of 2D materials: graphene, MoS2 and imogolite. Issue 9 (25th January 2018) - González, Rafael I.; Valencia, Felipe J.; Rogan, José; Valdivia, Juan Alejandro; Sofo, Jorge; Kiwi, Miguel; Munoz, Francisco
Abstract : The bending process of 2D materials, subject to an external force, is investigated, and applied to graphene, molybdenum disulphide (MoS2 ), and imogolite. Abstract : The bending process of 2D materials, subject to an external force, is investigated, and applied to graphene, molybdenum disulphide (MoS2 ), and imogolite. For graphene we obtained 3.43 eV Å 2 per atom for the bending modulus, which is in good agreement with the literature. We found that MoS2 is ∼11 times harder to bend than graphene, and has a bandgap variation of ∼1 eV as a function of curvature. Finally, we also used this strategy to study aluminosilicate nanotubes (imogolite) which, in contrast to graphene and MoS2, present an energy minimum for a finite curvature radius. Roof tile shaped imogolite precursors turn out to be stable, and thus are expected to be created during imogolite synthesis, as predicted to occur by self-assembly theory.